2021
DOI: 10.3947/ic.2021.0001
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of the Serovars and Antibiogram of Vibrio cholerae Isolates of the 2017 Ilorin Cholera Outbreak, Nigeria

Abstract: In this retrospective study, we determined the incidence, serovars, and antibiogram of Vibrio cholerae isolated from 102 clinical stool samples collected from rice water diarrheic patients during an outbreak (May - July 2017) in Ilorin metropolis, Nigeria. The culture positive rate of the V. cholerae isolates was 41.2%, with 41 and 1 isolates from O1 (Inaba) and non-O1/O139 serogroups, respectively. The isolates were the most susceptible to ciprofloxacin (76.2%) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…Although not isolated from this study, Vibrio cholerae, a pathogenic bacteria, has been isolated in other regions from aquaculture rearing facilities (Njoku et al, 2015) and has been implicated to account for several diarrhoea cases in Nigeria. For example, in the 2017 incident in the Ilorin metropolis, the culture positive rate of the Vibrio cholerae isolates was 41% (Amadu et al, 2021). Compared to the 78% level of occurrence reported by Borah et al (2010), Escherichia coli found in the present study was lower (8%) in both rearing enclosures and the regular trend recorded for other bacteria groups (TVC and TCC) was not witnessed for the faecal coliform group (Table 2 & 3).…”
Section: Discussioncontrasting
confidence: 70%
“…Although not isolated from this study, Vibrio cholerae, a pathogenic bacteria, has been isolated in other regions from aquaculture rearing facilities (Njoku et al, 2015) and has been implicated to account for several diarrhoea cases in Nigeria. For example, in the 2017 incident in the Ilorin metropolis, the culture positive rate of the Vibrio cholerae isolates was 41% (Amadu et al, 2021). Compared to the 78% level of occurrence reported by Borah et al (2010), Escherichia coli found in the present study was lower (8%) in both rearing enclosures and the regular trend recorded for other bacteria groups (TVC and TCC) was not witnessed for the faecal coliform group (Table 2 & 3).…”
Section: Discussioncontrasting
confidence: 70%
“…This is supported by different reports around the world. For example, the sero-prevalence of V. cholerae O1 was 60 to 86% in Bangladesh (38, 39), 100% in Pakistan) (40,41), and 59% in Nigeria (42,43). Evidences shown that in recent times, Ethiopia's con ict has erupted in Oromia and Amhara National Regional States.…”
Section: Discussionmentioning
confidence: 99%